Study on biological control model of Empoasca onukii Matsuda ‐take tea garden ecology as an example. Issue 12 (8th November 2021) - Sun, Jiazhao; Zhang, Lin; Li, Zizhao; Zou, Yunding; Bi, Shoudong
Abstract: The closeness of the spatial relationship between natural enemies and target pests directly affects the control effect of natural enemies on target pests. Therefore, we here use both geostatistics and cluster sample variance analysis methods to investigate the six kinds of natural enemies and pests in Huangshan large‐leaf tea garden at fall and winter of 2020. In this study, we firstly use the geostatistics method to calculate the geostatistical semivariogram variation range and then conduct the Grey correlation analysis on six main natural enemies of Empoasca onukii Matsuda . Our results indicate that the larger the correlation value is, the closer the natural enemy is to the target pest in space, and the top three natural enemies Clubiona japonicola, Oxyopes sertatus and Tetragnatha squamata are more closely related to Empoasca onukii Matsuda in space through the comprehensive judgment. Secondly, we use the cluster sample variance analysis method to calculate the basic sample square number and then perform the Grey correlation analysis on them. Our findings demonstrate that the top three natural enemies O. sertatus, T. squamata and Erigonidium graminicolum are more closely related to Empoasca onukii Matsuda in space via the comprehensive judgment. Remarkably, both O. sertatus and T. squamata have been revealed to be vital enemies of the Empoasca onukii Matsuda in tea garden. Overall, our study not only uncovers the spatial relationship between natural enemies and Empoasca onukii Matsuda, but also provides a scientific basis for further protecting and utilizing natural enemies to control pests in the tea garden.